Pengembangan Board Game Catur Matematika Sebagai Media Pembelajaran Pada Materi Matriks Serta Barisan Dan Deret - Farah Dita Auliya; Dian Oktaviani; Siti Ilmatul Ummah (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Nowadays, technological developments are very fast and sophisticated. This development has an impact on interactive learning in schools. Therefore, learning media is needed that is in line with the development of this technology. The goal is to make students more enthusiastic again. The aims of this research are: (1) to determine students' activeness in teaching and learning activities in mathematics for class XI students at SMAS Budaya Jakarta. (2) can produce interactive learning through this board game learning media with matrix material and rows and rows for class XI students at SMAS Budaya Jakarta. This development research method uses the ADDIE model analysis steps (Analysis, Design, Development, Implementation and Evaluation) because this step has an innovative and systematic system, thereby enabling researchers to achieve research objectives.